PENGARUH MOTIVASI, TINDAKAN SUPERVISI, PELATIHAN PROFESI, DAN PENGALAMAN AUDIT TERHADAP PROFESIONALISME AUDITOR PADA BADAN PEMERIKSA KEUANGAN (BPK) RI PERWAKILAN PROVINSI BALI - Clara Alverina; Made Yudi Darmita (Journal Research of Accounting, 2020)
Auditor professionalism is an attitude to maintain professional status and maintain a public image of himself, responsible to himself or responsible to applicable legal provisions. This study aims to examine how motivation (X1) influences auditor professionalism (Y), how supervision (X2) influences auditor professionalism (Y), how professional training (X3) influences auditor professionalism (Y) and how audit experience (X4) influences auditor professionalism (Y) and how the influence of motivation, supervision actions, professional training and audit experience on auditor professionalism at the BPK RI Representative of Bali Province. In this study using a purposive sampling method, namely auditors who worked more than 1 year at the BPK RI Representative of the Province of Bali. The population in this study were 47 people. Data analysis techniques in this study used Data Quality Test, Classical Assumption Test, t Test, F Test and Multiple Linear Regression Analysis. The results of this study indicate that motivation, supervision actions, and professional training have an effect on auditor professionalism while audit experience has no effect on auditor professionalism. And motivation, supervision, professional training, and audit experience together have an effect on auditor professionalism.Keywords: motivation, the act of supervision, professional training, audit experience, and auditors professionalism.